Rules versus Human Beings, and the Mandate of the ECB - Marcel Fratzscher (CESifo Economic Studies, 2016)
The actions by the European Central Bank (ECB) during the global and European crises have triggered a highly controversial debate, in particular in Germany, about the costs and benefits of the chosen policy path. The article reviews, compares, and evaluates the different arguments made in favor and against ECB policies around three key dimensions—the link of the policy path to price stability, financial stability, and economic policy. It argues that this debate is not only about the weighing of the benefits against the costs of monetary policy, but it is primarily about the question which mandate the ECB should pursue. This question remains unanswered.
Additional information: This is a pre-copyedited, author-produced PDF of an article accepted for publication in CESifo Economic Studies following peer review. The version of record Rules versus Human Beings, and the Mandate of the ECB / Marcel Fratzscher. In: CESifo Economic Studies 62 (2016), 1, p. 68-87 is available online at: http://dx.doi.org/10.1093/cesifo/ifv018
Keywords: E50; E60; E58; 330; mandate; price stability; financial stability; European Central Bank; Germany; unconventional policies